2019
DOI: 10.1111/are.14117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary vitamin B 6 supplementation on growth and intestinal microflora of juvenile golden pompano ( Trachinotus ovatus )

Abstract: In order to investigate the dietary vitamin B 6 (VB 6 ) requirement for juvenile golden pompano, an experiment of six different diets with six dietary VB 6 levels (0, 3.75, 7.47, 10.6, 13.7 and 18.5 mg/kg) was conducted. The results indicated that the content of dietary VB 6 significantly increased weight gain rate (WGR), specific growth rate (SGR) and feed conversion ratio (FCR; p < 0.05). Golden pompano fed diet containing 7.47 mg/kg VB 6 achieved the maximum ALT, AST, GPx, hepatic VB 6 concentrations as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…A transcriptome study of spotted sea bass ( Dicentrarchus punctatus ) revealed that lipid metabolism-related genes are highly expressed in SW-acclimated individuals ( Zhang et al, 2017 ). Dietary vitamin B6 affected oxidative stress, growth, and gut microbiota of golden pompano ( Trachinotus ovatus ) ( Huang et al, 2019 ). In our study, vitamin B6 was also higher in FW Asian sea bass.…”
Section: Discussionmentioning
confidence: 99%
“…A transcriptome study of spotted sea bass ( Dicentrarchus punctatus ) revealed that lipid metabolism-related genes are highly expressed in SW-acclimated individuals ( Zhang et al, 2017 ). Dietary vitamin B6 affected oxidative stress, growth, and gut microbiota of golden pompano ( Trachinotus ovatus ) ( Huang et al, 2019 ). In our study, vitamin B6 was also higher in FW Asian sea bass.…”
Section: Discussionmentioning
confidence: 99%
“…Pyridoxine (PN) is an indispensable nutrient for animals and has a powerful effect on a variety of physiological and biochemical processes, such as enhancing immune responses (Chen et al, 2005), prompting the absorption and metabolism of amino acids (Calderón‐Guzmán et al, 2004) and acting as a coenzyme for transaminases (Rogers & Mohan, 1994). The positive effects of PN on growth performance and immunity have been reported in various species (Huang et al, 2019; Khan & Khan, 2021; Liu et al, 2018; Saha et al, 2016; Zehra & Khan, 2018). Our previous studies indicated that dietary supplementation with PN promoted grass carp growth, immunity and structural integrity in various organs (intestine, spleen, head kidney and gill), which helps to improve resistance to pathogens (Jiang et al, 2019; Wu et al, 2018; Zheng et al, 2017, 2020).…”
Section: Introductionmentioning
confidence: 92%
“…Diet composition -these include proteins (Gajardo et al 2017;Nyman et al 2017;Parma et al 2016;Schmidt et al 2016), lipids (Castro et al 2019You et al 2019;Yu et al 2019), carbohydrates (Gatesoupe et al 2014;Zhao et al 2020), vitamins (Huang et al 2019;Xun et al 2019), probiotics (Jaramillo-Torres et al 2019Lauzon et al 2010), prebiotics (Gupta et al 2019;Li et al 2019b;Su et al 2017), and many other additives (Dai et al 2020;Luo et al 2020;Piazzon et al 2017), and diet processing technologies (Barreto-Curiel et al 2018)-may induce changes in the gut microbiota of marine fish. More detailed effects of diet on the gut microbiota of aquatic animals may be found in the review by Ringø et al (2016).…”
Section: Dietmentioning
confidence: 99%